Essentials in Bone and Soft-Tissue Pathology - Khurana, Jasvir S.; McCarthy, Edward F.; Zhang, Paul J.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2010)
Essentials in Bone and Soft-Tissue Pathology is a concise and well-illustrated handbook that captures the salient points of the most common problems in bone and soft-tissue pathology. The volume includes the most important diagnostic features of common musculoskeletal lesions. This book is a short text directed primarily at residents in pathology and other individuals interested in the field of orthopedic pathology, including medical students, orthopedic surgeons, radiologists, and practicing pathologists who do not see these cases on a day to day basis. Jasvir S. Khurana, MD has trained in orthopedic surgery as well as pathology. He trained in Boston at the Massachusetts General Hospital and Tufts New England Medical Center and did a fellowship at the Mayo Clinic. He was on faculty at the University of Pennsylvania and is currently an associate professor in pathology and a surgical pathologist at Temple University in Philadelphia, with a special interest in bone. His research interests include bone tumors and bone biology. He has authored several papers and text books in the field of orthopedic pathology. Edward McCarthy, MD has trained in orthopedic surgery as well as pathology. He trained in Iowa and Maryland where he also did his fellowship in orthopedic pathology. He has been on faculty at Johns Hopkins Hospital for several years where he is currently a professor of pathology. He has received several awards for clinical work and teaching. His clinical and research interests include bone and joint diseases including the use of undecalcified sections for the study of metabolic bone disease. He has authored several papers and text books in the field of orthopedic pathology. Paul J. Zhang, MD trained at the New York University and did a fellowship at the Memorial Sloan-Kettering Cancer Center. He has worked at the Roswell Park Cancer Institute and is currently an associate professor of pathology at the University of Pennsylvania, where he is the director of Bone and Soft-tissue service. His main research interest is in soft-tissue sarcoma where he has authored numerous papers.
Bone Structure, Development and Bone Biology -- Common Problems in Orthopedic Pathology Including Trauma, Reactive Conditions and Necrosis of Bone -- Arthropathies -- Infections of Bones -- Metabolic Bone Disorders -- Tumors and Tumor-Like Lesions of Bone -- Tumors and Tumor-Like Lesions of the Soft-Tissues.
Keywords: Pathology; Pathology